2021
DOI: 10.1111/jocn.15964
|View full text |Cite
|
Sign up to set email alerts
|

Otago exercise programme for physical function and mental health among older adults with cognitive frailty during COVID‐19: A randomised controlled trial

Abstract: Aims and ObjectivesQuarantine during the COVID‐19 pandemic resulted in longer‐term sedentary behaviours and mental health problems. Our study aimed to evaluate the impact of the Otago exercise programme (OEP) on physical function and mental health among elderly with cognitive frailty during COVID‐19.BackgroundLockdowns and restrictions during the COVID‐19 pandemic result in longer‐term sedentary behaviours related disease and mental problem. Older people with cognitive frailty are more vulnerable to be influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 58 publications
1
51
2
Order By: Relevance
“…The inducing and influencing factors of hypertension include biological, social and psychological aspects [12]. On the basis of drug treatment, experts advocate a healthy lifestyle and correct stress-coping strategies to prevent hypertension [13][14][15][16][17]. Previous studies have shown that hypertension is a common risk factor for physical frailty and cognitive decline [18].…”
Section: Introductionmentioning
confidence: 99%
“…The inducing and influencing factors of hypertension include biological, social and psychological aspects [12]. On the basis of drug treatment, experts advocate a healthy lifestyle and correct stress-coping strategies to prevent hypertension [13][14][15][16][17]. Previous studies have shown that hypertension is a common risk factor for physical frailty and cognitive decline [18].…”
Section: Introductionmentioning
confidence: 99%
“…Maximizing the challenge did not appear to be a priority in recent published studies, which either do not comment on efforts to individualize the intervention [ 21 , 22 ] or allude to progressing the group as a whole [ 23 ]. Chen et al [ 20 ] mention that physiotherapists “guided” participants to modify their exercise level, but the weights used were consistent at 0.5 kg and nurses “led” the intervention, so it is not clear how often physiotherapists may have guided these changes.…”
Section: Discussionmentioning
confidence: 99%
“…), and Kovàcs et al delivered the program with two physiotherapists for groups of 2–4 participants [ 19 ]. Recently, a series of studies in nursing home settings has supported the feasibility of group OEP with residents with physical and cognitive frailty [ 20 , 21 , 22 , 23 ]. While the mean MMSE scores of participants represent cognitive impairment (21–22/30) [ 20 , 21 ], a diagnosis of dementia was not in the inclusion criteria of any of these studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations